Beware the drink trap - Abd Razak, Dzulkifli (2005)
I spent a lot of my money on booze, birds and fast cars the rest i just squandered. AS the festivals approach, more and more advertisements on alcohol and alcoholic beverages are appearing in the mass media, enticing the people to drink. But let us all, drinkers and all, look at the life of Best, whom Pele called "the greatest footballer in the world". Signing on as an amateur for Manchester United in 1961, Best’s football career had been meteoric. Within two years he signed a professional contract with United and made his English League debut. Before long the football world became aware of his talents.